Validity of Japanese version of a two-item 60-minute moderate-to-vigorous physical activity screening tool for compliance with WHO physical activity recommendations - Akira Kyan; Shigeho Tanaka; Minoru Takakura; Timothy Olds; Natasha Schranz; Chiaki Tanaka (Japanese Society of Physical Fitness and Sports Medicine, 2021)
The aim of this study was to examine the validity of a Japanese version of the physical activity (PA) question of the Patient-Centered Assessment and Counseling for Exercise Plus Nutrition (PACE+), which is globally used to assess compliance with the WHO PA recommendation for youth. Analyses included 80 Japanese upper elementary students and 44 Japanese junior high students. Consistency of the classification of achieving/not achieving the PA recommendation between the two methods (PACE+ and ActiGraph accelerometry) was assessed by calculating percentage agreement rate, sensitivity, and specificity. Spearman rank correlation (𝜌) was applied to assess the correlation between the two methods. The percentage agreement in upper elementary students and junior high students was 83.8% and 65.9%, respectively. While the sensitivity and specificity of the scale in assessing the compliance of upper elementary students with PA recommendation were 8.3% and 97.1%, respectively, and for junior high school students 42.9% and 76.7%, respectively. The correlation coefficients between PACE+ and accelerometry for elementary and junior high school students were 0.13 and 0.50, respectively. The validity of PACE+ among Japanese adolescents was confirmed similarly to previous studies conducted in other countries. However, it should be viewed with caution that PACE+ may underestimate the proportion of children achieving PA recommendations.